Effect of waves on cavitation and pressure pulses of a tanker with twin podded propulsion. (April 2017) - Taskar, Bhushan; Steen, Sverre; Eriksson, Jonas
Highlights: Tanker with twin podded propulsion was simulated in waves using CFD to obtain wake variation. Effect of wake change, ship motions, RPM variation and speed loss has been studied. Significant increase in cavitation and pressure pulses was observed in waves. It is found that having a wake data in waves could be beneficial for designing a propeller. Abstract: There is increasing interest in optimizing ships for the actual operating condition rather than just for calm water. In order to optimize the propeller designs for operations in waves, it is essential to study how the propeller performance is affected by operation in waves. The effect of various factors that influence the propeller is quantified in this paper using a 8000 dwt chemical tanker equipped with twin-podded propulsion as a case vessel. Propeller performance in waves in terms of cavitation, pressure pulses, and efficiency is compared with the performance in calm water. The influence of wake variation, ship motions, RPM fluctuations and speed loss is studied. Substantial increase in cavitation and pressure pulses due to wake variation in the presence of waves is found. It is found that the effect of other factors is relatively small and easier to take into account as compared to wake variation. Therefore, considering the wake variation at least in the critical wave condition (where the wavelength is close to ship length) in addition to calm water wake is recommended in order to ensure that the optimized propeller performs well both in calm water and in waves.